Increasing Work Achievement Through Motivation - Tarigan, Dinarta; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Today, human resources are more important to the success of an organization than ever before. Many companies understand that having human capital can give them a competitive advantage. The phenomenon that occurs in the Medan City Branch of the Medan City Branch and the North Medan Branch is that the leader's way of managing is unsuitable with a leadership style that is not compatible with other employees so that the employee does not respect the leader, by leading employees by indifferently paying attention to his employees. Lack of achievement from employees is due to a lack of motivation given to employees so that employees only do their work without creating new innovations and good creativity, employees also do not want to give their all because they are afraid of being taken advantage of and not given more intensity. This often happens in where employees have more abilities will be utilized by the organization without any incentives and bonuses are given to someone who has more abilities, especially those who have good achievements in the company. The results of this research are as follows: Leadership Style has a positive and significant effect on Work Motivation with an original sample value of 0.766 and a p value of 0.000 <0.05. Leadership style has a positive and significant effect on work performance with an original sample value of 0.355 and a p value of 0.024 <0.05. Work Motivation has a positive and significant effect on Work Performance with an original sample value of 0.572 and a p value of 0.001 <0.05. Leadership style has a positive and significant indirect effect on work performance through work motivation with a value of 0.438 and a p value of 0.000 <0.05.